A vulnerabilidade e segurança alimentar dos países da União Econômica e Monetária da África Ocidental (UEMOA) - Monteiro, Marcelino Armindo (2019)
This research analyzed the productive structures and the population vulnerability in the regions of the countries of the Economic and Monetary Union of West Africa. The periods of analysis were different according to the instruments and the specific objective to be examined. In the regional analysis of the productive structures it consisted of a predetermined cut of the years 1991/2001/2010/2016 and, in the analysis of the population vulnerability, the periods were in a sequence according to the availability of the data of each country, from 2013 to 2018 The work hypothesis states that Availability and Access to food and other services are not major factors for population vulnerability in the regions of the eight WAEMU countries. The theoretical contribution was initiated with the classical theorists of this field, from von Thunen to the most recent ones, Walter Isard, and to allow for the more robustness of the work the Douglass North conceptions were treated and complementing the discussion were brought authors such as Christaller, Myrdal, Perroux and Hirschman. Subsequently, to meet the vulnerability analysis objective, it relied on reports from FAO, UNDP and some contemporary researchers such as Chambers. In the diversification of livelihoods to reduce vulnerability, authors Van der Ploeg and Frank Ellis were brought in. The methodology applied was the qualitative-quantitative analysis, with a regional analysis instrument, such as: Location Quotient (QL), Location Coefficient (CL), Redistribution Coefficient (RC), Specialization Coefficient (CE) and Coefficient of Restructuring (CReest.) In the first part and Vulnerability Analysis and Mapping (VAM) was applied in the second part, conducted in part the Major Components Factor Analysis. In both cases, the data applied were secondary. In the regional analysis, were data from World Bank; for the vulnerability analysis, the FAO and the National Institutes of Research data from each UEMOA country were analyzed. The results showed that the UEMOA productive structures are specialized and in some cases the tendency is to diversify, as seen in the QL analysis. Thus, presented by each country, in each period evaluated, was four (4) QLs> 1 and the maximum number nine (9), in the 15 analyzed activities. Thus, in a universe of 15 products, a country with 8 or more QLs> 1 indicates that in its portfolio it presents something above 53% of the productive specialization in the country. In general, WAEMU countries are moving towards productive specialization, but in any case, the tendency to diversify has been consistently strengthened, as presented in various activities. With CReest's analysis, it was thus possible to state that the productive structures of Guinea-Bissau in 1991/2001 and 2001/2010 and Togo in 2010/2016 are not similar to the structure of the productive activities of the reference region (UEMOA), with the other six countries having a productive structure very close to UEMOA. The VAM results showed that WAEMU countries are between Phase three (F3) and four (F4). With this, it can be seen that in the territory of UEMOA live the people with situation of medium and high vulnerability. From the analysis's answers, it can be concluded that Access and Instability are the two most important factors for negatively pressing the situation of vulnerability in WAEMU countries. Availability is not a major element in the pressure for greater vulnerability of WAEMU countries. This allows rejection of the study hypothesis.